Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
55 = 6x + 7 so 48 = 6x so 8 = x
The given expression can be simplified to: -6x-7
Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
6x - 8 + 2x - 5 = 7 - 2x ?
55 = 6x + 7 so 48 = 6x so 8 = x
The given expression can be simplified to: -6x-7
x=7
It is 6x+1 simplified
6x+3y = 8 3y = -6x+8 y = -3x+8/3 The slope of the line is -3
(-3,-1)
5x + 8 = 3x + 25x - 3x = 2 - 82x = -6x = -6/2x = -3Check:5(-3) + 8 = 3(-3) + 2-15 + 8 = -9 + 2-7 = -7
It is an expression that can be simplified to: 6x+1